Evaluasi Tata Kelola Teknologi Informasi Menggunakan Kerangka Kerja Cobit 5 Pada Gelato Secrets - Ayu Manik Dirgayusari; Desak Made Dwi Utami Putra; Ni Wayan Rika Andini (INFORMAL: Informatics Journal, 2021)
Many people have benefited from the use of information technology, one of which is in the trade business sector. One company that is engaged in manufacture that utilizes information technology in its operational processes is Gelato Secrets. Its efforts to support business goals have been supported by an Information System (SI) which is still relatively new to be implemented in Gelato Secrets, namely the Odoo application that supports the sales process in each outlet. To evaluate the maturity level of information technology governance in the Odoo application, a framework is needed as a reference model to ensure the quality of IT governance in the application of the "Odoo" application. Control Objective for Information and related Technology (COBIT) is a best practice that provides an organization's entire business process and describes it in a logical structure of activities that can be managed and controlled effectively. The results of the research, measuring the average level of capability obtained, have only reached the Established Process level, which means that each sub-domain has been well defined and standardized. This shows that almost all processes meet the requirements, but there are still weaknesses on the side of system changes caused by the absence of an adequate documentation process. The company still has to fulfill the level 5 process, namely Optimizing Process by means of regular training to HR about existing Information Systems and also fulfilling user needs such as adding menus that can facilitate the smooth running of business processes in order to meet the expected company targets, as well as adding more technology devices. Information needed by the company in sufficient quantities.